2018
DOI: 10.1111/jeb.13274
|View full text |Cite
|
Sign up to set email alerts
|

Do parasites and antioxidant availability affect begging behaviour, growth rate and resistance to oxidative stress?

Abstract: Early-life trade-offs faced by developing offspring can have long-term consequences for their future fitness. Young offspring use begging displays to solicit resources from their parents and have been selected to grow fast to maximize survival. However, growth and begging behaviour are generally traded off against self-maintenance. Oxidative stress, a physiological mediator of life-history trade-offs, may play a major role in this trade-off by constraining, or being costly to, growth and begging behaviour. Yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
3
2
0
Order By: Relevance
“…Thus, as the nestling adaptive immune system matures, the costs of flea parasitism may be reduced and a larger proportion of the food provided by the parents can be allocated to growth. Interestingly, in our study, these differences had vanished at the age of 14 days mirroring results from other studies on flea manipulation of great and blue tits (Tripet et al 2002, Maronde et al 2018). As our flea manipulation was confined to the incubation phase, natural population dynamics (including immigration and emigration) might have evened out the differences late in the nestling cycle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, as the nestling adaptive immune system matures, the costs of flea parasitism may be reduced and a larger proportion of the food provided by the parents can be allocated to growth. Interestingly, in our study, these differences had vanished at the age of 14 days mirroring results from other studies on flea manipulation of great and blue tits (Tripet et al 2002, Maronde et al 2018). As our flea manipulation was confined to the incubation phase, natural population dynamics (including immigration and emigration) might have evened out the differences late in the nestling cycle.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, as the nestling adaptive immune system matures, the costs of flea parasitism may be reduced and a larger proportion of the food provided by the parents can be allocated to growth. Interestingly, in our study, these differences had vanished at the age of 14 days mirroring results from other studies on flea manipulation of great and blue tits (Tripet et al 2002, Maronde et al 2018).…”
Section: Brood Sizesupporting
confidence: 91%
“…This may reflect a poorer capacity of parasitized females to buffer reproduction-associated oxidative increases or a potential delayed effect of parasites. Generally, similar flea infestation studies have largely found no results of parasites on oxidative stress (Devevey et al, 2008;Maronde et al, 2018;Wegmann et al, 2015). That said, our finding of an interaction between parasitism and oxidative stress where others have found no relationship is not surprising given the multifaceted and non-linear relationship between the two (Costantini and MĂžller, 2009).…”
Section: Oxidative Stress and Immunitysupporting
confidence: 46%
“…Larcombe et al (2008) showed that the yellow plumage colouration in blue tit nestlings was positively related with lipid peroxidation levels, suggesting that colouration reflected the oxidative damage rather than resistance to oxidative stress. In our study, nests with added grass had more fleas, which has been related to increased oxidative stress in female great tit (Parus major) nestlings (De Coster et al (2012) but see Maronde et al (2018)). Hence, stronger carotenoid-based colouration in nestling' flanges could reflect oxidative damage as a consequence of flea infestation and related inflammation processes (Owen et al 2010).…”
Section: Discussionmentioning
confidence: 55%